2020
DOI: 10.1097/prs.0000000000006673
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Early Tongue Reduction Surgery for Macroglossia in Beckwith-Wiedemann Syndrome

Abstract: Background: Macroglossia, a cardinal feature of the (epi)genetic disorder Beckwith-Wiedemann syndrome, is associated with obstructive sleep apnea, speech and/or feeding difficulties, and dental or jaw malalignment. These sequelae may be treated and/or prevented with tongue reduction surgery; the authors sought to determine whether certain Beckwith-Wiedemann syndrome patients may benefit from early surgical intervention before age 12 months. Methods: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 47 publications
0
15
1
3
Order By: Relevance
“…Immediate postoperative extubation without need for reintubation was achieved in 100% of the cases, with no related complications reported. These results contrast with what is commonly seen in the literature, which often reports maintaining postoperative intubation for 24 to 120 hours (Celiker et al, 2004; Batra and Valecha, 2014; Cohen et al, 2020). Immediate postoperative extubation reduces the risks associated with intubation such as damage to laryngeal structures, edema, and aspiration (Divatia & Bhowmick, 2005), as well as the risks associated with extended hospital stays, such as infection, and the financial costs associated with such stays (Dasta et al, 2005).…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Immediate postoperative extubation without need for reintubation was achieved in 100% of the cases, with no related complications reported. These results contrast with what is commonly seen in the literature, which often reports maintaining postoperative intubation for 24 to 120 hours (Celiker et al, 2004; Batra and Valecha, 2014; Cohen et al, 2020). Immediate postoperative extubation reduces the risks associated with intubation such as damage to laryngeal structures, edema, and aspiration (Divatia & Bhowmick, 2005), as well as the risks associated with extended hospital stays, such as infection, and the financial costs associated with such stays (Dasta et al, 2005).…”
Section: Discussioncontrasting
confidence: 97%
“…The large tongue often leads to concern that intubation will be difficult at inception of the case and that postoperative intubation may be necessary at its conclusion (Shott, 2001; Batra & Valecha, 2014). Patients are often kept intubated for several days after surgery, including in patients not otherwise dependent on respiratory support for chronic respiratory concerns (Naujokat et al, 2019; Cohen et al, 2020). There is additional concern regarding intraoperative hemorrhage and need for transfusion due to the vascularity of the tongue and young age of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies reported that the increased pressure of the tongue results in anterior open bite and a prognathic mandibular appearance secondary to an abnormally obtuse gonial angle and increased mandibular length, which can lead to negative consequences in social acceptance, projection of self-image, and psychological well-being [ 20 , 32 ]. Indeed, TRS represents the second most common surgical intervention after repair of omphalocele in patients with BWS, and it is currently recommended to correct the obstruction of the upper airways, sleep apnea, feeding difficulties or language delay, and to prevent musculoskeletal and dentoalveolar malformations [ 33 , 34 ]. Taking into account the invasiveness of TRS, its impact on breathing, language and quality of life, it is paramount to define whether BWS individuals really benefit from this procedure to prevent dentofacial deformities [ 18 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resections involving the tip and anterior tongue primarily target the length, marginal excisions target the width, and central resections address the thickness. Different craniofacial centers have reported using different tongue reduction techniques with distinct incision patterns and methods of cautery including keyhole, stellate, anterior wedge, and modified W-shaped patterns (Balaji, 2013; Chau et al, 2011; Cohen et al, 2020; Gardon et al, 2019; Heggie et al, 2013; Hettinger and Denny, 2011; Kacker et al, 2000; Kadouch et al, 2012; Mixter et al, 1993; Tomlinson et al, 2007; Wang et al, 2003; Yilmaz et al, 2009). There is currently no consensus as to which approach is the standard.…”
Section: Discussionmentioning
confidence: 99%
“…The most common manifestation is true macroglossia secondary to enlargement of the tongue musculature, which is reportedly seen in 80% to 99% of patients with BWS (Tomlinson et al, 2007; Kadouch et al, 2012; Maas et al, 2016b; Simmonds et al, 2018; Wang et al, 2020). Macroglossia has been reported to result in sequelae such as speech anomalies, feeding and swallowing problems, airway obstruction, malocclusion, oral incompetence, drooling, recurrent lingual trauma, cosmetic concerns, and psychosocial issues (Shipster et al, 2012; Van Lierde et al, 2012; Balaji, 2013; Alonso-Rodriguez et al, 2018; Cielo et al, 2019; Cohen et al, 2020). Surgical tongue reduction, also known as glossectomy, is the only available method of correction.…”
Section: Introductionmentioning
confidence: 99%